Metagenomic Analysis Reveals Microbial Community Structure and Metabolic Potential for Nitrogen Acquisition in the Oligotrophic Surface Water of the Indian Ocean - Wang, Yayu; Liao, Shuilin; Gai, Yingbao; Liu, Guilin; Jin, Tao; Liu, Huan; Gram, Lone; Strube, Mikael Lenz; Fan, Guangyi; Sahu, Sunil Kumar; Liu, Shanshan; Gan, Shuheng; et al. (Frontiers in Microbiology, 2021)
Despite being the world’s third largest ocean, the Indian Ocean is one of the least studied and understood with respect to microbial diversity as well as biogeochemical and ecological functions. In this study, we investigated the microbial community and its metabolic potential for nitrogen (N) acquisition in the oligotrophic surface waters of the Indian Ocean using a metagenomic approach. Proteobacteria and Cyanobacteria dominated the microbial community with an average 37.85% and 23.56% of relative abundance, respectively, followed by Bacteroidetes (3.73%), Actinobacteria (1.69%), Firmicutes (0.76%), Verrucomicrobia (0.36%) and Planctomycetes (0.31%). Overall, only 24.3% of functional genes were common among all sampling stations indicating a high level of gene diversity. However, the presence of 82.6% common KEGG Orthology (KOs) in all samples showed high functional redundancy across the Indian Ocean. Temperature, phosphate, silicate and pH were important environmental factors regulating the microbial distribution in the Indian Ocean. The cyanobacterial genus Prochlorococcus was abundant with an average 17.4% of relative abundance in the surface waters, and while 54 Prochlorococcus genomes were detected, 53 were grouped mainly within HLII clade. In total, 179 of 234 Prochlorococcus sequences extracted from the global ocean dataset were clustered into HL clades and exhibited less divergence, but 55 sequences of LL clades presented more divergence exhibiting different branch length. The genes encoding enzymes related to ammonia metabolism, such as urease, glutamate dehydrogenase, ammonia transporter and nitrilase presented higher abundances than the genes involved in inorganic N assimilation in both microbial community and metagenomic Prochlorococcus population. Furthermore, genes associated with dissimilatory nitrate reduction, denitrification, nitrogen fixation, nitrification and anammox were absent in metagenome Prochlorococcus population, i.e., nitrogenase and nitrate reductase. Notably, the de novo biosynthesis pathways of six different amino acids were incomplete in the metagenomic Prochlorococcus population and Prochlorococcus genomes, suggesting compensatory uptake of these amino acids from the environment. These results reveal the features of the taxonomic and functional structure of the Indian Ocean microbiome and their adaptive strategies to ambient N deficiency in the oligotrophic ocean.